Missed Opportunities : Innovation and Resource-Based Growth in Latin America - Maloney, William F. (World Bank, Washington, DC, 2014)
Latin America missed opportunities for rapid resource-based growth that similarly endowed countries-Australia, Canada, Scandinavia-were able to take advantage of. Fundamental to this poor performance was deficient technological adoption driven by two factors. First, deficient national "learning" or "innovative" capacity, arising from low investment in human capital and scientific infrastructure, led to weak ability to innovate or even take advantage of technological advances abroad. Second, the period of inward-looking industrialization discouraged innovation and created a sector whose growth depended on artificial monopoly rents rather than the quasi-rents arising from technological adoption, and at the same time undermined resource-intensive sectors that had the potential for dynamic growth.